2022
DOI: 10.1097/wco.0000000000001101
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 associated myopathy

Abstract: Purpose of reviewThe global spread of severe acute respiratory syndrome coronavirus 2 resulted in many cases of acute and postacute muscular symptoms. In this review, we try to decipher the potential underlying pathomechanisms and summarize the potential links between viral infection and muscle affection. Recent findingsDisregarding single case studies that do not allow safe conclusions due to the high number of infections, histopathological evidence of myositis has only been reported in deceased individuals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 83 publications
3
5
0
Order By: Relevance
“…Upper leg MRI also did not reveal signs of myositis, which is consistent with recently published radiological findings (50). However, biopsies were taken almost a year after acute infection and several case reports of biopsy-proven myositis after SARS-CoV-2 have been published (51)(52)(53), and we ourselves histologically diagnosed non-specific myositis in some patients in the subacute aftermath of mild or moderate COVID (Fig. S3F).…”
Section: Discussionsupporting
confidence: 90%
“…Upper leg MRI also did not reveal signs of myositis, which is consistent with recently published radiological findings (50). However, biopsies were taken almost a year after acute infection and several case reports of biopsy-proven myositis after SARS-CoV-2 have been published (51)(52)(53), and we ourselves histologically diagnosed non-specific myositis in some patients in the subacute aftermath of mild or moderate COVID (Fig. S3F).…”
Section: Discussionsupporting
confidence: 90%
“…Very few studies have documented formal evaluation of muscle weakness in acute settings and none exist for acute COVID infections. 23 We found that most of our patients had demonstrable muscle weakness with around one third having a degree of weakness similar to other inflammatory myopathy cohorts. 24 Reduction in muscle strength by almost 30% in presymptomatic COVID-19 was reported in one patient.…”
Section: Discussionsupporting
confidence: 74%
“…Demonstrable muscle weakness, particularly of neck flexor muscles, and disability that limits daily activities were common. Very few studies have documented formal evaluation of muscle weakness in acute settings and none exist for acute COVID infections 23 . We found that most of our patients had demonstrable muscle weakness with around one third having a degree of weakness similar to other inflammatory myopathy cohorts 24 .…”
Section: Discussionmentioning
confidence: 58%
“…Myopathy has also been reported in some patients during the acute phase of infection [ 60 ]. It is not clear if this is due to the direct effect of the virus on myocytes or due to the local and/or systemic immune response against the invading virus [ 75 ].…”
Section: Neurological Manifestations Of Sars-cov-2mentioning
confidence: 99%